Body Sensors and Electrocardiography - Trobec, Roman (SpringerBriefs in Applied Sciences and Technology,, 2018)
This monograph presents a comprehensive overview of the electrocardiography from the aspect of wireless and mobile monitoring and its potential for personalized health management. The topical focus is on the implementation and efficient application of user friendly m-Health systems. The target audience comprises biomedical engineers, medical doctors, students, industrial experts and health managers developing m-Health solutions.